2006
DOI: 10.1111/j.1365-2036.2006.03098.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of pegylated‐interferon‐α2a plus ribavirin with or without amantadine in the re‐treatment of patients with chronic hepatitis C not responding to standard interferon and ribavirin

Abstract: SUMMARY BackgroundThere is yet no established treatment for chronic hepatitis C patients non-responder to standard interferon and ribavirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The main features of the trials included in the meta-analysis are shown in Table 2 in Appendix. Fourteen, which accounted for 3898 patients, were reported as full papers [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Among the trials, three studies did not report the number of participating centers, while all remaining studies were multicenter trials, with the number of centers ranging from 2 to 133; among these studies 8 reported data on the prevalence of patients with cirrhosis (357/1282 = 27.8%).…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main features of the trials included in the meta-analysis are shown in Table 2 in Appendix. Fourteen, which accounted for 3898 patients, were reported as full papers [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Among the trials, three studies did not report the number of participating centers, while all remaining studies were multicenter trials, with the number of centers ranging from 2 to 133; among these studies 8 reported data on the prevalence of patients with cirrhosis (357/1282 = 27.8%).…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Of the remaining 42 full-text articles, 30 were excluded because they did not meet inclusion criteria, leaving 14 fulllength papers [3][4][5][6][7][8][9][10][11][12][13][14][15][16] meeting criteria for inclusion in the meta-analysis. Finally, 6 abstracts identified by manual search [17][18][19][20][21][22], were also included, only for the evaluation of the publication bias.…”
Section: Selection Of Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses in all groups are less than in individuals receiving pegylated interferon and ribavirin de novo [214][215][216]. When re-treatment is considered, all modifiable factors known to affect response should be changed to meet optimal conditions, where possible.…”
Section: Nonresponders and Relapsersmentioning
confidence: 99%
“…In the HIVnegative population, re-treatment may be considered in individuals who have failed to respond with an SVR to non-gold standard therapy, i.e. nonpegylated interferon with or without ribavirin, or in individuals with progression of fibrosis [215,216].…”
Section: Nonresponders and Relapsersmentioning
confidence: 99%